2019
DOI: 10.7150/thno.29546
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repositioning Inferred from E2F1-Coregulator Interactions Studies for the Prevention and Treatment of Metastatic Cancers

Abstract: Metastasis management remains a long-standing challenge. High abundance of E2F1 triggers tumor progression by developing protein-protein interactions (PPI) with coregulators that enhance its potential to activate a network of prometastatic transcriptional targets. Methods: To identify E2F1-coregulators, we integrated high-throughput Co-immunoprecipitation (IP)/mass spectometry, GST-pull-down assays, and structure modeling. Potential inhibitors of PPI discovered were found by bioinformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…E2F1 promotes the invasiveness of urothelial bladder carcinoma 3 , 4 , 9 , 10 . To study the role of this transcription factor in bladder cancer progression, we utilized a human tissue culture model consisting of various cell lines that differ in their invasive potential according to the endogenous E2F1 expression status.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…E2F1 promotes the invasiveness of urothelial bladder carcinoma 3 , 4 , 9 , 10 . To study the role of this transcription factor in bladder cancer progression, we utilized a human tissue culture model consisting of various cell lines that differ in their invasive potential according to the endogenous E2F1 expression status.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main mechanisms is that they act as transcriptional regulators 61 . Notably, it was recently shown that E2F1 controls the expression of PCGs whose products in turn, physically associate with E2F1 to enhance transcription of prometastatic targets 6 , 9 , 72 . With this in mind, we hypothesized that this could be also the case for the nucleus-localized lncRNA-SLC16A1-AS1, which may interact with E2F1 to fine-tune transcription of E2F1-regulated targets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations